Experimental investigation of mechanical and microstructural properties of concrete containing bentonite and dolomite as a partial replacement of cement - Israr Ahmad Awan; Syed Saqib Mehboob; Raja Wajaht Zahoor Khan (Penerbit Universiti Kebangsaan Malaysia, 2023)
In this study, the effect of bentonite (BT) and dolomite (DT) on the mechanical and microstructural properties of concrete was evaluated on nine mixes. Cement was replaced with bentonite and dolomite by weight with varying mix ratios. The mixes are divided as M1 (Control mix), M2 (2.5% BT), M3 (2.5% DT), M4 (5% BT), M5 (5% DT), M6 (10% BT), M7 (10% DT), M8 (2.5% BT and 2.5% DT), and M9 (5% BT and 5% DT). Concrete specimens were subjected to mechanical and microstructural analysis tests. Mechanical test results show that the addition of bentonite (2.5%, 5%, and 10% ) leads to an increase in compressive strength (6.31%, 8.94%, and 13.15%) respectively. Similarly, the addition of 2.5% and 5% dolomite enhanced compressive strength by 10.52%, and 8.94% respectively, however, the addition of 10% dolomite reduced compressive strength by 6.8%. Replacement of cement with dolomite and bentonite individually also showed a small contribution to flexural and split tensile strength. Microstructural analysis shows that the addition of bentonite and dolomite filled the microstructure and refined the internal pores contributing to compressive strength. In addition, the replacement of cement with bentonite and dolomite enhanced the formation of CSH gel.Keywords: Bentonite; dolomite; mechanical properties; microstructural analysis